Impact of Crude Oil and Dispersant Use on the Baltic Sea Blue Mussel Mytilus trossulus Microbiome - Anna Reunamo; Raisa Turja; Jaak Truu; Kirsten S. Jørgensen (Applied Microbiology)
The Baltic Sea blue mussel (Mytilus trossulus) plays a crucial role in this brackish water ecosystem, filtering water and accumulating pollutants. This study investigated how exposure to crude oil and dispersants affects the microbiome of M. trossulus at two salinities (5.6 and 15) over 21 days. Results showed that dispersant use significantly increased the accumulation of polycyclic aromatic hydrocarbons (PAHs) in mussel tissues, particularly at lower salinity. The microbial communities in gills and digestive glands were notably affected, with shifts towards hydrocarbon-degrading bacteria like Shewanella and Acinetobacter in samples exposed to chemically enhanced water accommodated fraction of crude oil (CEWAF). Salinity was a key factor in determining both PAH accumulation and microbial diversity, with lower salinity leading to reduced bacterial diversity in dispersant treatments. This study highlights the need for a cautious use of dispersants in sensitive environments like the Baltic Sea, emphasizing the ecological implications of altered microbial communities.